Lost in the Vault?: Demonstration Sports at the Winter Olympics and How Digital Media Can Bring Them 'Back to the Future'. Issue 13 (2nd December 2020) - Ramon, Xavier; Xu, Qingru; Billings, Andrew C.
Abstract: Compared to the summer games, the winter Olympics hold a relatively limited sporting appeal, yet their importance and capacity to capture the public and media attention remain undisputable. For many years, in addition to events on the official programme, Olympic Games Organising Committees (OCOGs) have advanced demonstration sports, some of which then dissipated from the landscape while others moved to full medal status, including curling, ice dancing and short track speed skating. Followed by the decision in 1989 by the International Olympic Committee (IOC) to eliminate demonstration sports, these events made their last appearance at Albertville 1992. Nevertheless, other demonstration sports –military patrol, skijöring, dogsled racing, ice stock sport, winter pentathlon, bandy, speed skiing and ski ballet–occupy distinct realms of Olympic history, informing the history of the Olympic movement by what did or did not advance into mainstream competition. Resources and footage housed in the IOC historical archives focusing on demonstration sports at the winter games can be brought 'from the vault', via the Olympic Channel and its social media handles, to broaden citizens' appreciation of the cultural significance of demonstration sports at the winter games and understanding of the Olympics in the process.